2013
DOI: 10.1021/nl400374z
|View full text |Cite
|
Sign up to set email alerts
|

Colossal Absorption of Molecules Inside Single Terahertz Nanoantennas

Abstract: Molecules have extremely small absorption cross sections in the terahertz range even under resonant conditions, which severely limit their detectability, often requiring tens of milligrams. We demonstrate that nanoantennas tailored for the terahertz range resolves the small molecular cross section problem. The extremely asymmetric electromagnetic environment inside the slot antenna, which finds the electric field being enhanced by thousand times with the magnetic field changed little, forces the molecular cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
161
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 196 publications
(163 citation statements)
references
References 49 publications
2
161
0
Order By: Relevance
“…This indicates the sensitivity is higher as the gap width decreases. Gap-width dependent sensitivities have been reported for slot antenna structures but have not been reported for metamaterial patterns with positive structures [4,18]. Furthermore, the detection volume has not been addressed as a function of the gap width.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates the sensitivity is higher as the gap width decreases. Gap-width dependent sensitivities have been reported for slot antenna structures but have not been reported for metamaterial patterns with positive structures [4,18]. Furthermore, the detection volume has not been addressed as a function of the gap width.…”
Section: Resultsmentioning
confidence: 99%
“…Among them negative slot or slit antenna structures possess the advantage of backgroundfree exclusive electromagnetic funneling when operated in transmission geometry, and is, therefore, capable of experimentally determining the near-field enhancement at the gap [19]. Such properties are advantageous in applications where quantitative analyses are highly required, such as in nonlinear experiments [10,[20][21][22] or when realizing molecular absorption or scattering enhancement [23][24][25]. Physical origins of the observed phenomena are mostly interpreted in terms of changes in transmission spectra, while the reflection counterpart, an excellent additional source of information, is usually not considered in the transmission type nanogaps.…”
Section: Introductionmentioning
confidence: 99%
“…By investigating the frequency shifts of the resonances resulting from the structures of metamaterials or antennas, small amounts of bacteria can be effectively detected. A previous study detailing THz antennas for the detection of molecules demonstrated that a sensitivity enhancement of at least three orders of magnitude can be achieved using antennas with a 5-μm-wide slot (Park et al 2013). Thus, the sensitivity can be further improved by optimizing the antenna structure to be compatible with bacterial cells.…”
Section: Discussionmentioning
confidence: 99%